Research on mapping algorithm of virtual network oriented to SDN - Jian WANG; Guo-sheng ZHAO; Zhi-xin LI (Tongxin xuebao)
In order to solve the problem of virtual network mapping,a mapping method based on ant colony hybrid genetic algorithm was put forward under SDN environment,which established a linear programming model for virtual network mapping,and divided the mapping process into node mapping and link mapping.Firstly,the fusion algorithm was adopted,in which virtual nodes were mapped to physical nodes.Then the shortest path algorithm was used to map the virtual link to a physical link.On this basis,the acceptance ratio of virtual network requests can be improved.Simulation experiment results show that acceptance rate of virtual network requests can be increased by 10% efficiently using the ant colony hybrid genetic algorithm,compared with existing mapping algorithms D-ViNE,RW-BFS and R-ViNE.Further more,proposed method can greatly improve the average utilization rate of nodes and links and the ratio of the mapping income to cost.